2010
DOI: 10.1007/s10499-010-9326-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of additive iron on growth, tissue distribution, haematology and immunology of gilthead sea bream, Sparus aurata

Abstract: The comparative effects of iron-supplemented levels on growth, tissue distribution, haematology and immunology of gilthead sea bream, Sparus aurata (2 g) were investigated, using four organic (50, 100, 200, 300 mg ORG/kg diet) and one inorganic iron source (200 INOR mg/kg diet). Fish were treated for 12 weeks with the experimental diets and maintained at a water temperature of 19-22°C. Growth (final weight and specific growth rate), tissue distribution (spleen, liver and muscle), haematological parameters (red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 25 publications
(33 reference statements)
0
11
0
1
Order By: Relevance
“…A significant effect of the lipid source on erythrocyte count was confirmed by Demska-Zakęś et al (2012) for Tinca tinca. Rigos et al (2010) reported an increase in RBC of S. aurata fed with food supplemented with iron. A positive effect of probiotic supplementation on the RBC value of Astronotus ocellatus was reported by Firouzbakhsh et al (2011).…”
Section: Erythrocytesmentioning
confidence: 99%
“…A significant effect of the lipid source on erythrocyte count was confirmed by Demska-Zakęś et al (2012) for Tinca tinca. Rigos et al (2010) reported an increase in RBC of S. aurata fed with food supplemented with iron. A positive effect of probiotic supplementation on the RBC value of Astronotus ocellatus was reported by Firouzbakhsh et al (2011).…”
Section: Erythrocytesmentioning
confidence: 99%
“…The hemoglobin concentration was determined using a miniaturized version of the Drabkin method (Rigos et al, 2010).…”
Section: Histological Hematological and Immunological Parametersmentioning
confidence: 99%
“…Rigos et al 4. fed the Gilthead seabream with Fe supplementary feed (i.e., 5–309 mg Fe/kg feed) for 12 weeks, but no significant difference was detected in growth and tissue Fe distribution among different Fe treatments4. Similar results were also found in the Fe nutritional studies on Atlantic salmon ( Salmo salar ), yellowtail ( Seriola quinqueradiata ), tilapia ( Oreochromis niloticus×O.…”
mentioning
confidence: 69%
“…Over a certain supplementary level (typically >30 mg Fe/kg feed), the dose-dependent response was not obvious in most of the feeding experiments2. Rigos et al 4. fed the Gilthead seabream with Fe supplementary feed (i.e., 5–309 mg Fe/kg feed) for 12 weeks, but no significant difference was detected in growth and tissue Fe distribution among different Fe treatments4.…”
mentioning
confidence: 99%